Determinants of loss to care and risk of clinical progression in PLWH who are re-engaged in care after a temporary loss - Mussini, Cristina; Lorenzini, Patrizia; Cozzi-Lepri, Alessandro; Mammone, Alessia; Guaraldi, Giovanni; Marchetti, Giulia; Lichtner, Miriam; Lapadula, Giuseppe; Lo Caputo, Sergio; Antinori, Andrea; d'Arminio Monforte, Antonella; Girardi, Enrico; et al. (Scientific Reports, 2021)
The risk of developing AIDS is elevated not only among those with a late HIV diagnosis but also among those lost to care (LTC). The aims were to address the risk of becoming LTC and of clinical progression in LTC patients who re-enter care. Patients were defined as LTC if they had no visit for ≥ 18 months. Of these, persons with subsequent visits were defined as re-engaged in care (RIC). Factors associated with becoming LTC and RIC were investigated. The risk of disease progression was estimated by comparing RIC with patients continuously followed. Over 11,285 individuals included, 3962 became LTC, and of these, 1062 were RIC. Older age, presentation with AIDS and with higher HIV-RNA were associated with a reduced risk of LTC. In contrast, lower education level, irregular job, being an immigrant and injecting-drug user were associated with an increased LTC probability. Moreover, RIC with HIV-RNA > 200 copies/mL at the re-entry had a higher risk of clinical progression, while those with HIV-RNA ≤ 200 copies/mL had a higher risk of only non-AIDS progression. Patients re-entering care after being LTC appeared to be at higher risk of clinical progression than those continuously in care. Active strategies for re-engagement in care should be promoted.